Respostas

A melhor resposta!
2014-07-18T21:30:37-03:00
Δ= b² - 4 .a. c
a= -2x²
b= 3x
c= -5

Δ= 3² -4. (-2). (-5)
Δ= 9 - 40
Δ= -31   ⇒ quando Δ for negativo não poussui raiz, logo não precisa achar o x e o x'.


Espero ter ajudado!!!
1 5 1
2014-07-18T21:44:44-03:00
Δ= b^{2}-4.a.c
 

Δ= 3^{2}-4.(-2).(5)
Δ=9-(-40)
Δ=49

x = -b \frac{+}{-} √Δ
                   2.a
x'= -3+√49
      2.(-2)
x'= -3+7
       -4
x'= \frac{-7}{4}





x''= -3-√49
      2.(-2)  
 x''=  -3-7
         -4
x''=  \frac{-10}{-4}
 x''=  \frac{5}{2}